Occurrence of Salmonella spp. in the broiler production chain - Queiroz, A. C. [UNESP] (2023)
Brazilian chicken meat is exported to more than 150 countries and consumed by consumer markets that demand high quality and food safety, thus, requiring very strict control of pathogens present in food to guarantee these rigorous safety standards. This study evaluates the reports from the Salmonella spp. Control and Monitoring Program of the Brazilian Ministry of Agriculture, Livestock and Food Supply of seven slaughterhouses inspected by the Federal Inspection Service from the western region of Paraná state, Brazil, from March 2017 to February 2019. The broiler litter swab and carcass analyses revealed a Salmonella spp. positivity ratio of 5.9% (19/319) and 23.5% (75/319), respectively. The concomitant presence of Salmonella spp. in the broiler litter swab and chicken carcasses occurred in 58% of the positive samples. The most frequently isolated serovar in the carcasses was Salmonella Heidelberg (85.3%) followed by Salmonella spp. (10.6%). During slaughter, carcass positivity to Salmonella spp. was significantly different (p=0.047) between the first (19.6%) and the second (29.4%) shifts. The results alert for the possibility of carcass contamination during slaughtering and, therefore, more stringent hygiene measures between shifts must be implemented to mitigate carcass contamination.